If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 139 + -1u = 217 Solving 139 + -1u = 217 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-139' to each side of the equation. 139 + -139 + -1u = 217 + -139 Combine like terms: 139 + -139 = 0 0 + -1u = 217 + -139 -1u = 217 + -139 Combine like terms: 217 + -139 = 78 -1u = 78 Divide each side by '-1'. u = -78 Simplifying u = -78
| -19+17u=18u+1 | | 3-x+4x+6-2x+1= | | -2(3x+1)=10 | | -14+18g=16g+14 | | -x+2(-2x+16)=-8 | | x=10.5y | | -x-4x+16=-8 | | x+y+2y+-2x+z+5x-y= | | 6y-3=2y+15 | | 2(x-2)-16=8-2x | | 13q+8=9q | | -x^5+2x^4-4x^3= | | 9x-63=4x+22 | | s+6=8(9) | | 6m+2(m+7)=m | | x-6=66-15(x+8) | | -14x+9+7x=-12 | | 4-(-2)(3)= | | x-6=66-15 | | 10e^3x-e=2e^3x | | -119=-17n | | 6+4x=3(3x+2)-x | | 2g-g-h+3h+2h-h= | | 12u-18=8u-6-1u-8 | | 3b^3-192= | | k-10-4k=10-k | | 215= | | 4-5y=(-16) | | 6+4c=3(3x+2)-x | | 3x-10-5x=-24 | | 9x-12+5x=3 | | 7=7x-3(6x+8) |